KOMPONEN DAN KESESUAIAN HABITAT LUTUNG DAHI PUTIH (Presbytis frontata) DI DAS CANTUNG - Darmaji, Darmaji; Fithria, Abdi; Kissinger, Kissinger; Priatmadi, Bambang Joko (Universitas Lambung Mangkurat, 2023)
The white-fronted langur (Presbytis frontata) is categorised as a protected wildlife according to (P.106/MENLHK/SETJEN/KUM.1/8/2018). Forest degradation, land use change, and environmental damage due to human activities by encroaching on forests can cause habitat fragmentation. The preservation of white-fronted langurs may be threatened by degraded or unsuitable habitat conditions. This study aims to analyse the characteristics and components of white-fronted langur habitat and to analyse the suitability of white-fronted langur habitat in the Cantung watershed area of Kota Baru district, South Kalimantan. The research was conducted in September-October 2021. Data collection using the roaming method.This study concluded that there were 31 habitat distribution points with 72 individuals of white-fronted langurs observed. White-fronted langurs in the Cantung watershed area were found at an altitude of 5-85 m above sea level, optimal temperature of 20°-32°C, humidity of 78-95%, distance from water sources 200-500 m, distance from roads <200-600 m, locations with plantation land cover, dry land agriculture, mixed gardens and mining. The suitability of white-fronted langur habitat in the Cantung Watershed Area based on 6 habitat components shows the highest scoring value of 3 (high level of suitability).